Word of Mouth dan Media Sosial terhadap Minat Beli Konsumen pada Kafe Kenalin Ini Kopi di Universitas Buana Perjuangan Karawang - Nopri Hardianto; N.Neni Triana; Thomas Nadeak (IPM2KPE, 2024)
This research aims to test and analyze the influence of word of mouth and social media on consumer purchasing interest at the